AB0486 ANALYSIS OF 89 PATIENTS WITH GIANT CELL ARTERITIS FROM TURKEY: PET-CT AS AN EMERGING METHOD FOR DIAGNOSIS AND HIGH FLARE RATE WITH STANDARD CARE. (2nd June 2020) - Ince, B.; Artan, S.; Yalçinkaya, Y.; Artim-Esen, B.; Gül, A.; Ocal, M. L.; Inanc, M.
Abstract : Background: The prevalence of giant cell arteritis (GCA) in Turkey has been reported lower than other European countries and the information on clinical patterns, diagnostic modalities, treatment and prognosis of GCA are limited (1). Objectives: We aimed to analyse our GCA cohort from a large outpatient clinic for the last 20 years. Methods: Data of the GCA patients followed up at least for 6 months in our vasculitis clinic between 1998 and 2018 evaluated retrospectively according to EULAR 2018 GCA clinical research recommendations (2). Chi-square, students t-test, logistic regression analysis and Kaplan-Meier test were used for statistical analysis. Results: Eighty-nine patients with adequate follow-up data (64% female, mean age 67.9 ± 9.1) were analysed. Median follow up duration was 46 months (3-256) and mean time to diagnosis after presenting symptom (TTD) was 5, 9±1, 2 months (0-60). Polymyalgia rheumatica was found in 36 (40.4%) patients. The clinical findings of the patients are shown in Table-1. Mean TTD was longer in patients with acute vision loss (AVL) (11±4 vs. 4, 8±1, 1 months p=0.002). Mean CRP was 90, 7±82 (8-343) mg/L and ESR was 103, 7±25 (52-138) mm/h at the time of diagnosis. Mean age was lower (63±2 vs 69±1 p=0.01); mean CRP (141, 8±107, 3 vs. 76, 6±67, 9 mg/dL p=0.023) and ESR (120, 8±25, 1 vs. 99, 3±24, 3 mm/h p=0.004) was higher in patients without cranial symptoms (extracranial GCA group). PET-CT findings compatible with large vessel vasculitis were present in 64% (34/53). Sixteen of 19 (%84, 2) patients in the extracranial GCA group had positive PET-CT. Temporal artery (TA) biopsy positivity was 64% (34/53). Sensitivity of ACR 1990 Criteria was 77, 5% and GIACTA study inclusion criteria was 58, 4% in this cohort at diagnosis. Fullfilment of GIACTA criteria was still present in 12 (13, 5%) patients after six months of follow up. Treatment data was shown in table-2. Total flare rate was 34, 8% and flare risk was lower in the extracranial GCA group (3/20 vs. 28/69 p=0.035 OR=0.78 %95 CI 0.64 – 0.96). Reduced survival was observed in cases diagnosed older than 65 years (168, 8±23, 9 vs 209±17, 3 months p=0, 015). Conclusion: The analysis of the largest single center cohort from Turkey confirmed that delayed diagnosis is associated with vision loss. A subgroup of patients without apparent cranial symptoms but positive PET-CT findings is delineated. These patients are younger, present with higher inflammatory response and fewer relapses. The sensitivity of ACR criteria in our cohort is less than 80%. High flare rate especially in GCA patients with cranial symptoms and GIACTA criteria fullfilment after 6 months of treatment in more than 10% of the patients show a need for for new treatment options. References: [1]Pamuk, O.N., et al., Giant cell arteritis and polymyalgia rheumatica in northwestern Turkey: Clinical features and epidemiological data. Clin Exp Rheumatol, 2009. 27 (5): p. 830-3. [2]Ehlers, L., et al., 2018 EULAR recommendations for a core data set to support observational research and clinical care in giant cell arteritis. Ann Rheum Dis, 2019. 78 (9): p. 1160-1166. Disclosure of Interests: None declared